Analysis and Implementation of New Product Development Method: Case Study of Asikin Aja - Ramadhan, Saddam; Prasetio, Eko Agus (Journal of Innovation, Business and Entrepreneurship, 2019)
Abstract. The culinary subsector is the largest industry that dominates 41.69% of the overall creative economy. Asikin Aja is one of the SMEs engaged in the culinary field. This company has developed many culinary products, but none of them are successful in entering the market. By using fishbone analysis, it is known that Asikin Aja experiences various kinds of problems. Lack understanding of customer demand, poor team management, and poor product development plans make it difficult for Asikin to develop new products. To overcome the problems faced by Asikin Aja, the right method is needed. There are four methods that are analyzed, i.e., Kanban, Waterfall, Scrum, and Lean Startup. After conducting the analysis, Lean Startup is selected as the suitable method for solving product development problems at Asikin Aja. After selecting the method, researcher creates a plan and implements it directly by making a minimum viable product. By conducting product tests directly to customers, the value and growth hypothesis can be fulfilled in one iteration which will be followed by persevere that is producing and selling the product.Keywords: Lean Startup, Framework, Team Management, Small Medium Enterprise, Culinary Industry